2020
DOI: 10.3390/life10110285
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Applying Hyaluronic Acid Gels in the Primary Prevention of Intrauterine Adhesion after Hysteroscopic Myomectomy: A Meta-Analysis of Randomized Controlled Trials

Abstract: Intrauterine adhesion (IUA), which mainly occurs after intrauterine surgery or an inflammatory process, is an important but often neglected condition in women of reproductive age. The presentation of IUA varies greatly, ranging from symptom-free to severe, with amenorrhea or infertility. With much advanced development of intrauterine instruments, more intrauterine diseases can be successfully cured by hysteroscopic surgery. Among these, submucosal myoma is one of the best examples. Submucosal myomas are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Our previous findings demonstrated that crosslinked hyaluronic acid gels are highly recommended for the prevention of intrauterine adhesions [ 86 ]. A pooled analysis of two studies that limited the use of ACHA in 119 women showed that the application of ACHA gel for the primary prevention of IUA in patients after hysteroscopic myomectomy led to a statistically significant reduction in the development of IUA postoperatively (OR 0.285, 95% CI 0.116–0.701, p = 0.006) [ 148 ]. All this suggests that using ACHA gel in patients after hysteroscopic myomectomy could significantly reduce de novo IUA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings demonstrated that crosslinked hyaluronic acid gels are highly recommended for the prevention of intrauterine adhesions [ 86 ]. A pooled analysis of two studies that limited the use of ACHA in 119 women showed that the application of ACHA gel for the primary prevention of IUA in patients after hysteroscopic myomectomy led to a statistically significant reduction in the development of IUA postoperatively (OR 0.285, 95% CI 0.116–0.701, p = 0.006) [ 148 ]. All this suggests that using ACHA gel in patients after hysteroscopic myomectomy could significantly reduce de novo IUA.…”
Section: Discussionmentioning
confidence: 99%
“…A barrier can be achieved by two strategies; one uses agents and the other is physical or mechanical. Agents act as a barrier, can be solid form, liquid form (hydroflotation agents) or gel form, and the components include polyethylene oxide–sodium carboxymethylcellulose gel and crosslinked hyaluronic acid (CHA) gels [ 71 , 81 , 82 , 96 , 97 , 98 , 99 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 120 , 148 , 149 , 154 , 155 , 156 ]. Physical or mechanical barriers include intrauterine suitable balloon catheters, Foley balloon catheters, Malecot catheters, silicone sheets, and intrauterine devices (IUD) [ 73 , 103 , 104 , 105 , 106 , 107 , 108 ].…”
Section: Primary Prevention Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
“… 19 Currently, hydrogels based on natural materials such as chitosan, gelatin, and hyaluronic acid have been used to prevent adhesion. 20 22 Due to their poor mechanical properties and rapid degradation, they are not yet able to achieve satisfactory treatment outcomes. In order to improve the physical properties of natural polymers and enhance their resistance to enzyme attacks, 23 light-activated materials play an increasingly important role in three-dimensional (3D) bioprinting technology.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research suggests that a GelMA hydrogel has good biological and adjustable physical properties, which allows cell proliferation and diffusion in GelMA hydrogel-based materials. 22 , 24 Collagen is the main component of the extracellular matrix (ECM), which is widely used in the field of biomaterials because of its good physical and chemical properties. 25 27 However, a pure collagen hydrogel has a single structure, simple properties, and poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Women treated with HA gels have a statistically significant lower incidence of IUAs than non-treated women (13% vs. 39%), and additionally, women receiving the HA gel treatment have a significantly reduced severity of IUA than women in the no-HA treatment group [7]. In the current special issue, based on the positive benefits of application of HA as a preventive strategy for patients after hysteroscopic myomectomy [7], a systematic review and meta-analysis was conducted to investigate the effect of HA on the primary prevention of IUA formation after hysteroscopic myomectomy [8]. A pooled analysis of three randomized controlled trials shows a statistically significant reduction in the development of IUA postoperatively, with an odd ratio (OR) of 0.29, and a 95% confidence interval (CI) of 0.12~0.70, suggesting that the use of HA gel in patients after hysteroscopic myomectomy can significantly reduce de novo IUA [8].…”
mentioning
confidence: 99%